Killer poker - Johnstone, J. A. (New York : Kensington Pub., 2011)
"Conrad Browning had money, a manservant and a mission: to find his missing children and meet them for the first time. He's come as far as Denver, dodged a bullet from a beautiful assassin, and landed in a big buy-in poker tournament against a ruthless heavy-betting cattle baron with a plan of his own - to take this city slicker into the wilderness, and hunt him like an animal."--Back cover.
Keywords: Shooters of firearms -- Fiction; Missing children -- Fiction; Poker -- Tournaments -- Fiction; Missing children; Poker -- Tournaments; Shooters of firearms; Western stories; Fiction